Pelatihan dan Pendampingan Penggunaan Aplikasi SIPD-RI oleh Bendahara Penerimaan dan Pengeluaran di BAPENDA Kabupaten Sumbawa - Salsa Septia Hernanda; Dina Lisdiantari; Subhan Purwadinata (Institut Nalanda, 2026)
This community service activity aims to improve understanding and skills in using the Regional Government Information System (SIPD-RI), particularly for revenue and expenditure treasurers at the Regional Revenue Agency (BAPENDA) of Sumbawa Regency. The method used is a descriptive qualitative approach through observation, documentation, and direct practice during the internship program. The activity was carried out through training and mentoring stages, including system introduction, application practice, and evaluation of encountered constraints. The results indicate an improvement in students’ understanding and skills in managing digital-based regional finance, especially in revenue administration processes such as inputting data from SAMSAT, cash receipts, and taxpayer payments (BIL), as well as understanding supporting documents such as STBP and STS. Additionally, students gained knowledge of expenditure processes through the preparation of payment orders (SPM) in SIPD-RI. However, technical issues such as system errors and limited user understanding remain challenges. Therefore, training and mentoring play an important role in enhancing the effectiveness of SIPD-RI utilization and supporting transparency and accountability in regional financial management.